The burden of atopic dermatitis and bacterial skin infections among urban‐living Indigenous children and young people in high‐income countries: A systematic review. Issue 1 (9th November 2022) - Ricciardo, Bernadette M.; Kessaris, Heather‐Lynn; Kumarasinghe, Prasad; Carapetis, Jonathan R.; Bowen, Asha C.
Abstract: Background: A high burden of bacterial skin infections (BSI) is well documented in remote‐living Indigenous children and young people (CYP) in high‐income countries (HIC). Atopic dermatitis (AD) is the most common chronic inflammatory skin condition seen in CYP and predisposes to BSI. Despite the rate of urbanization for Indigenous people increasing globally, research is lacking on the burden of AD and BSI for urban‐living Indigenous CYP in HIC. Indigenous people in HIC share a history of colonization, displacement and subsequent ongoing negative impacts on health. Objective: To provide a global background on the burden of AD and BSI in urban‐living Indigenous CYP in HIC. Methods: A systematic review of primary observational studies on AD and BSI in English containing epidemiologic data was performed. MEDLINE, EMBASE, EMCARE, Web of Science, and PubMed databases were searched for articles between January 1990 and December 2021. Results: From 2278 original manuscripts, 16 were included: seven manuscripts documenting eight studies on AD; and nine manuscripts documenting nine studies on BSI. Current and severe symptoms of AD were more common in urban‐living Indigenous CYP in HIC compared with their non‐Indigenous peers, with children having a higher prevalence than adolescents. Urban‐living Indigenous CYP in HIC had a higher incidence of all measures of BSI compared with their non‐Indigenous peers, and were over‐represented for all measures of BSI compared with their proportion of the background population. Limitations include incomplete representation of all Indigenous populations in HIC. Conclusion: A significant burden of AD and BSI exists in urban‐living Indigenous CYP in HIC.